Strategies that enhance students access to public technical training institutions in Kenya - Nganyi, Jason Esiokhunjila; Odebero, Stephen Onyango; Onderi, Henry; Musera, Geofrey; Shigogodi, Josphat Mulama; Shigogodi, Josphat Mulama (HRMARS, 2014)
Stakeholders in the education sector in Kenya are concerned about low students’ participation in Technical Training Institutions. Despite the Government of Kenya’s efforts to upgrade infrastructure in these institutions, students’ participation has remained low yet the realization of Vision 2030 depends on middle level training. Therefore, this study was conceptualized to establish strategies adopted by Technical Training Institutions to support students access in these institutions. This study was conducted in Western Region of Kenya. Western Region comprise of the former Western, Nyanza and rift valley Provinces. The sample constituted of 200 lecturers (principals, deputy principals, heads of departments and registrars) and 400 students from 30 Technical Training Institutions. Data was collected using questionnaires. The results show that the strategies used to attract students are bursaries, provision of competitive courses and opening more centres. However, these strategies do not attract students to these Technical Training Institutions because of weak administration and implementation by the institutions. It was recommended that in an effort to promote enrolment in Technical Training Institutions, the Kenyan Government should fully fund students enrolled in Technical Training Institutions. Besides Technical Training Institutions should enhance advertisement of the courses offered; strengthen distance/e-learning; and review courses offered to meet the market demand.
DOI: 10.6007/IJARBSS/v4-i11/1273